Sosialisasi Dan Pendampingan Pendidikan Dusun Dedel Kulon Kecamatan Semanu Gunung Kidul Yogyakarta - Hillaya, Tanza Dwiki Riza; Wardani, Reinny Kusuma; Zulkarnain, Ilyas; An Naffi, hyan Adi; Rahmalia, Mayra Vega; Rahmawati, Alma Liana; Nugraha, Angga Febian; Septiawan, Andre Dwi; Lestari, Tri Aji; Utama, Satria (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Community service program aims to enhance educational support and empower MSMEs in Dusun Dedel Kulon. The implementation methods include socialization, mentoring, and direct consultation with the local community to ensure an inclusive and participatory approach. The findings indicate that there is a pressing need for improved education in Dusun Dedel Kulon. The active involvement of the community in training sessions, along with the enhancement of MSME skills, demonstrates a growing awareness and capacity to manage businesses more effectively